EXPLORING THE JURIDICAL FRAMEWORK FOR ENVIRONMENTALCONSERVATION WITHIN THE CONTEXT OF INFRASTRUCTURE DEVELOPMENT AND SUSTAINABLE PROGRESS IN THE REPUBLIC OF INDONESIA - Usman Tahir; Ramdan Yusuf; Gunawan Widjaja; Hadenan Towpek; Ekha Sri Sugiarti (ADISAM Publisher, 2024)
This paper delves into the intricate juridical framework governing environmental conservation within the dynamic context of infrastructure development and the pursuit of sustainable progress in the Republic of Indonesia. As Indonesia experiences rapid economic growth and urbanization, driven by ambitious infrastructure projects, it confronts a challenging dichotomy—simultaneously fostering development and preserving its ecological riches. This study offers an extensive examination of Indonesia's legal landscape, encompassing environmental laws, regulations, policies, and practical implementation and enforcement mechanisms. It scrutinizes the critical role of Environmental Impact Assessments (EIAs) in navigating the environmental consequences of infrastructure ventures. Additionally, it explores government policies and international commitments that underscore Indonesia's dedication to sustainability. The paper highlights the intrinsic connection between environmental conservation and sustainable progress, emphasizing the importance of responsible resource management and ecological preservation in achieving long-term development objectives. By analyzing case studies, policy implications, and future research directions, this research aims to provide a comprehensive understanding of how Indonesia can harmonize its infrastructure development ambitions with the imperative of environmental protection, ultimately guiding the nation toward a more sustainable and equitable future.